2012
DOI: 10.1111/j.1526-4610.2012.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue Therapy for Acute Migraine, Part 3: Opioids, NSAIDs, Steroids, and Post‐Discharge Medications

Abstract: Objective.-The final section of this 3-part review analyzes published reports involving the acute treatment of migraine with opioids, non-steroidal anti-inflammatory drugs (NSAIDs), and steroids in the emergency department (ED), urgent care, and headache clinic settings, as well as post-discharge medications. In the Conclusion, there is a general discussion of all the therapies presented in the 3 sections.Method.-Using the terms ("migraine" AND "emergency") AND ("therapy" OR "treatment"), the author searched M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 49 publications
2
64
0
7
Order By: Relevance
“…Moreover, among studies about the efficacy of opioids as rescue medication for acute migraine in EDs recently revised, only one evidenced a superiority of meperidina 75 mg i.m. versus ketorolac 30 mg i.m., three reported superiority of competitors and eight reported similar results for opioids versus competitors such as DHE, metoclopramide, chlorpromazine, droperidol, and ketorolac [5]. In any case, opioids did not adequately restore the patient's ability to function.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, among studies about the efficacy of opioids as rescue medication for acute migraine in EDs recently revised, only one evidenced a superiority of meperidina 75 mg i.m. versus ketorolac 30 mg i.m., three reported superiority of competitors and eight reported similar results for opioids versus competitors such as DHE, metoclopramide, chlorpromazine, droperidol, and ketorolac [5]. In any case, opioids did not adequately restore the patient's ability to function.…”
mentioning
confidence: 89%
“…Use of opioids for treatment of migraine is controversial. Despite evidence-based guidelines do not recommend opioids as first-line treatment of migraine attacks [2][3][4], and no randomized controlled trial has shown any significant effect of opioids on migraine attacks when pain-free was the primary end-point of the study [5], their use in clinical practice [6][7][8] and, even more, in emergency departments (EDs) is very large, especially in USA and Canada [9,10]. Moreover, among studies about the efficacy of opioids as rescue medication for acute migraine in EDs recently revised, only one evidenced a superiority of meperidina 75 mg i.m.…”
mentioning
confidence: 99%
“…[4,5] Periferal sinir blokları tedaviye dirençli kronik migren hastalarında gittikçe artan miktarda kullanılmaktadır. İlk defa 1961 yılında Kerr beyin sapında C1-C2'den gelen sinirler ile trigeminal…”
Section: Pain a Riunclassified
“…Several medications including intravenous non-steroidal anti-inflammatory drugs, paracetamol, triptans, Phenothiazines, new atypical antipsychotics, metoclopramide and opioids have been proposed as the first line drugs in the treatment of migraine attack (1)(2)(3)(4)(5)(6). However, the low efficacy, potential complications of medications and the intolerance of some patients for oral route due to nausea and vomiting, establish a difficult situation in some migraine patients.…”
Section: Introductionmentioning
confidence: 99%